PENERAPAN DESIGN THINKING DALAM PERANCANGAN PROTOTYPE UI DAN UX PADA APLIKASI PEMINJAMAN RUANGAN PKM DI UNIVERSITAS WIDYATAMA - Naila Aura Addinillah; Dani Hamdani (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
This research is motivated by the manual system of room rental at the Student Activity Center (PKM) of Widyatama University, which often causes problems such as unclear information on room availability and schedule conflicts. This problem is important to study because it has an impact on the efficiency of campus facility usage. Therefore, this study aims to design a prototype of a room rental application based on the Design Thinking method that focuses on user needs. The method used is Design Thinking with a descriptive qualitative approach. Data were collected through interviews, observations, and surveys, then analyzed using usability testing with the System Usability Scale (SUS) and Maze. The results of this study involved 22 participants in the usability test, consisting of 20 students as users and 2 admins as admins. Usability testing was carried out using the System Usability Scale (SUS) and Maze, with an average SUS score of 82.10 (user) and 83 (admin). This study shows that the Design Thinking approach is effective in designing a user-friendly room rental application. Based on these results, the study concluded that this application is worthy of further development. This study recommends further development at the implementation stage of web-based and mobile applications as well as expanding usability evaluation to more diverse user groups. Thus, it is expected that the designed system can be implemented in real terms to support the smooth running of student activities in the campus environment.